Tb-based cubic phase magneto-optical crystal and preparation method thereof
Through Tb3+ doped Re2O3 and ZrO2 combination materials and cold crucible technology, large-size, high Verdet coefficient, and strong laser damage threshold were grown, which solved the problem of insufficient performance of existing TGG magneto-optical crystals and realized the Preparation of low-cost, high-performance magneto-optical crystals.
Patent Information
- Application Number
- CN202411635887.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The Verdet coefficient, laser damage threshold and crystal size of existing TGG magneto-optical crystals are insufficient, making it difficult to meet the needs of high-power large-pulse magneto-optical devices.
Using a combination of Tb3+ doped Re2O3 and ZrO2, large-sized Tb-based cubic phase magneto-optical crystals are grown through cold crucible technology, thereby increasing their Verdet coefficient and laser damage threshold.
A new Tb-based magneto-optical crystal with large size, high Verdet coefficient, and strong laser damage threshold has been achieved, reducing production costs and meeting the needs of high-power large-pulse magneto-optical devices.
Smart Images

Figure CN119411228A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of magneto-optical crystals, and in particular, relates to a Tb-based cubic phase magneto-optical crystal and a preparation method thereof. Background Art
[0002] Magneto-optical crystals are crystals with magneto-optical effect. Magneto-optical crystals are widely used in magneto-optical modulators, laser isolators, optical storage, optical communications, laser gyroscopes and many other fields related to the national economy and people's livelihood due to their advantages of large Faraday rotation angle, rich magnetic phase change, high magnetic resonance frequency and strong optical magnetic coupling ability.
[0003] Magneto-optical crystals have good optical transmittance and moderate thermal conductivity, especially the commercially used yttrium iron garnet crystal (Y3FeO 12 , YIG) and terbium gallium garnet crystal (Tb3Ga5O 12 , TGG), among which YIG is limited by its light transmission range and is often used in infrared optical communication bands (≥1.3 μm), while TGG is mostly used in the visible to near-infrared wave (near 1.0 μm) band. With the development of high-power laser technology, especially high-power fiber lasers in the near-infrared band (1.03 μm), whose output power is as high as kilowatts or even tens of thousands of watts, there is an urgent need to reduce various thermal effects to avoid laser damage and thermal damage, which in turn puts higher and higher requirements on magneto-optical crystals; a higher Verdet coefficient can reduce the size of magneto-optical devices; a larger thermal conductivity is conducive to alleviating various thermal effects in the process; and an enhanced laser damage threshold can increase the power that can withstand the laser. However, the Verdet coefficient of commercial TGG crystals is 39-42 rad·m -1 ·T -1 (at 1064 nm), laser damage threshold 1.14 GW / cm 2 (1064 nm, 10 ns) need to be improved, and the crystal size is limited to Φ 50 mm×70 mm, and an iridium crucible is required during growth, so the growth cost is relatively high.
[0004] Therefore, further exploration of Tb 3+ It is imperative to develop new magneto-optical crystal materials to achieve large size, large Verdet coefficient, and strong laser damage threshold, paving the way for size reduction and compact magneto-optical device design to meet the development needs of low-cost, high-power, large-pulse magneto-optical devices. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a Tb-based cubic phase magneto-optical crystal and a preparation method thereof, which at least achieves the purpose of increasing the crystal size and improving the magneto-optical performance.
[0006] To solve the above problems, according to one aspect of the present invention, a Tb-based cubic magneto-optical crystal is provided. 3+ One or a combination of doped Re2O3 and ZrO2, wherein Re is a rare earth element selected from Y, Lu or Sc.
[0007] As a preferred embodiment, 10% at <Tb 3+ The doping concentration is ≤98%at.
[0008] As a preferred embodiment, 20%at≤Tb 3+ The doping concentration is ≤50%at.
[0009] As a preferred embodiment, the magneto-optical Verdet coefficient of the Tb-based cubic phase magneto-optical crystal is 10-149 rad·m -1 ·T -1 (at 1064 nm).
[0010] As a preferred embodiment, the magneto-optical Verdet coefficient is 35-73 rad·m -1 ·T -1 (at 1064 nm).
[0011] As a preferred embodiment, the transmittance range of the Tb-based cubic phase magneto-optical crystal is 400 nm-1100 nm.
[0012] The method for preparing the Tb-based cubic magneto-optical crystal according to the present invention is characterized by comprising: Step 1, weigh the raw materials Tb4O7, Re2O3, and ZrO2 according to the stoichiometric ratio, mix them thoroughly, put them into a high-frequency heater, heat them to near the melting point of the raw materials, and then keep them warm; Step 2, cooling to room temperature, taking out the reactants and selecting block crystals therein; Step three, annealing the bulk crystal obtained in step two in an argon-hydrogen mixed gas atmosphere to obtain the transparent Tb-based cubic phase magneto-optical crystal.
[0013] As a preferred embodiment, in step 1, the temperature is increased at 5°C per minute until it reaches near the melting point of the raw material, and the temperature is kept for 48 hours.
[0014] As a preferred embodiment, in step 2, the temperature is lowered from 10°C to room temperature.
[0015] As a preferred embodiment, in step three, the annealing conditions are: temperature 1500° C., time 48 hours.
[0016] The method proposed in the present invention of growing large-sized cubic phase magneto-optical crystals using cold crucible technology changes the disadvantages of high cost of the traditional pulling method and limited size of the floating zone method, and can obtain new Tb-based magneto-optical crystals with large size, high Verdet coefficient, strong laser damage threshold and low cost to meet the development needs of high-power large-pulse magneto-optical devices.
[0017] The present invention adopts cold crucible technology which does not involve the use of precious metal crucibles, and has a huge one-time output and a short growth cycle, which can greatly reduce production costs. Secondly, the grown magneto-optical crystal belongs to the cubic crystal system, and a suitable matrix can be selected according to demand, and its highest Verdet coefficient is 2-4 times that of TGG. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a schematic diagram of the structure of the growth device used in the present invention; in the figure, 1 is the molten shell cover, 2 is the molten shell lining, 3 is the water-cooled copper tube, 4 is the high-frequency coil, 5 is the melt, 6 is the crystal, 7 is the unmelted material, and 8 is the water-cooled seat.
[0019] Figure 2 This is a picture of a 10at% Tb:Y2O3 / ZrO2 crystal sample in Example 1; Figure 3 Figure 2 shows the 20at% Tb:Y2O3 / ZrO2 crystal blank and crystal sample in the embodiment; Figure 4 The 50at%Tb:Y2O3 / ZrO2 crystal blank and crystal sample in Example 3; Figure 5 This is a crystal diagram of 50at% Tb:Y2O3 in Example 4; Figure 6 This is a photo of the 50at% Tb:Y2O3 / ZrO2 crystal after annealing in Example 3; Figure 7 This is a picture of the Tb2O3 crystal sample in Example 5; Figure 8 The crystal XRD pattern obtained for the present invention; Fig. 9 This is the transmission spectrum of the 10at% Tb:Y2O3 / ZrO2 crystal in Example 1; Fig.10 This is the transmission spectrum of the 20at% Tb:Y2O3 / ZrO2 crystal in Example 2; Fig.11 This is the transmission spectrum of the 50at% Tb:Y2O3 / ZrO2 crystal in Example 3; Fig.12 This is the transmission spectrum of 50at% Tb:Y2O3 crystal in Example 4; Fig.13is the transmission spectrum of Tb2O3 crystal in Example 5; Fig.14 This is the magneto-optical performance diagram of 20at% Tb:Y2O3 / ZrO2 crystal in Example 2; Fig.15 This is the magneto-optical performance diagram of 50at%Tb:Y2O3 / ZrO2 crystal in Example 3; Fig.16 This is a diagram of the magneto-optical properties of 50at% Tb:Y2O3 crystal in Example 4; Fig.17 This is the magneto-optical properties diagram of Tb2O3 crystal in Example 5. DETAILED DESCRIPTION
[0020] A typical embodiment of the present invention provides a Tb-based cubic magneto-optical crystal, which is Tb 3+ Doped Re2O3, ZrO2 or a combination of both, wherein Re is a rare earth element (Re=Y, Lu, Sc), such as Tb:ZrO2, Tb:Re2O3, Tb:Re2O3 / ZrO2.
[0021] In the Tb-based cubic magneto-optical crystal provided above, 10% at <Tb 3+ The doping concentration is ≤98%at, more preferably 20%at <Tb 3+ The doping concentration is ≤50%at. The magneto-optical Verdet coefficient varies with Tb 3+ It increases with the increase of concentration (positively correlated). When the doping concentration is 98%at, it is Tb2O3 crystal.
[0022] The Tb-based cubic magneto-optical crystal described in this embodiment has a conductive matrix material and a cubic crystal structure. The light transmission range is 400 nm-1100 nm, and the magneto-optical Verdet coefficient is 10-149 rad·m -1 ·T -1 (at 1064nm), can be used in laser isolators, fiber signal amplifiers, 5G base stations, etc.
[0023] Cold crucible technology is a technology for growing crystals from melts. Its characteristic is that the crystal growth is not carried out in a crucible of metal materials, but is heated by high-frequency electromagnetic fields. The raw material itself is used as a crucible to melt the inside, and a cooling device is installed on the outside, so that the surface layer is not melted, forming an unmelted shell, which plays the role of a crucible. The crystal material that has been melted inside is separated from the heating zone by the crucible's descent, and the temperature gradually drops and the crystal grows.
[0024] Another typical embodiment of the present invention is to provide a method for growing Tb-based cubic phase magneto-optical crystals using cold crucible technology. The method includes the following steps 1 to 3. The structure of the growth device used in the embodiment of the present invention is as follows: Figure 1 shown.
[0025] Step 1: weigh the raw materials Tb4O7, Re2O3, and ZrO2 according to the stoichiometric ratio, mix them thoroughly, put them into a high-frequency heater, heat them to near the melting point of the raw materials, and then keep them warm. The heating rate and temperature are adjusted to make the mixed raw materials completely melted. The preferred heating rate and insulation time are to heat at 5°C per minute until the melting point of the raw materials is reached, and keep them warm for 48 hours.
[0026] Among them, the raw materials are Tb4O7, Re2O3 (Re=Y, Lu, Sc), and ZrO2, among which the melting point of Tb:Re2O3 is 2400-2550°C, the melting point of Tb:ZrO2 is 2600-2750°C, and the melting point of Tb:Re2O3 / ZrO2 is between 2450-2600°C. The specific melting point of the material depends on the doping concentration and the mixing ratio.
[0027] Step 2: Cooling down to room temperature, taking out the reactants and selecting bulk crystals with high optical quality.
[0028] In this step, the temperature is lowered at a relatively fast rate, for example, from 10°C to room temperature. By cooling, the molten raw materials undergo spontaneous crystallization, and then bulk crystals grow. After cooling to room temperature, block single crystals with high optical quality that are visually uniform in color and free of cracks are selected, and broken crystals and those with growth envelopes and uneven colors are recycled for reuse.
[0029] Step three, annealing the block crystals obtained in step two in an argon hydrogen (Ar+H2) mixed gas atmosphere. The annealing temperature is preferably 1500°C and kept warm for 48 hours. The purpose is to uniformly reduce the valence state of Tb ions in the crystal to 3+, exert the best magnetic effect, and finally obtain the Tb-based cubic phase magneto-optical crystal.
[0030] According to the above implementation method, the required oxide raw materials are first fully ground and mixed. Then the mixture is placed in a cold pot and heated at high temperature. The mixture is completely melted by adjusting the heating rate and temperature, and the temperature is kept constant for several hours, and then the temperature is quickly lowered. Finally, annealing is performed in a reducing atmosphere to obtain large-sized crystals. The magneto-optical crystals obtained by this scheme have good optical quality, large crystal size, high yield, and strong magneto-optical properties. No precious metals are used in the production process, which can effectively break through the size limitations of existing magneto-optical crystals and solve the problem of high production costs of existing processes.
[0031] The technical scheme claimed in the present invention is further described below by some examples. However, the examples and comparative examples are used to explain the embodiments of the present invention and do not exceed the scope of the subject matter of the present invention. The protection scope of the present invention is not limited by the examples. Unless otherwise specified, the materials and reagents used in the present invention can be obtained from commercial products in the art.
[0032] Example 1 Growth of 10at% Tb:Y2O3 / ZrO2 crystals using cold crucible technology The raw materials are Tb4O7, Y2O3, and ZrO2, which are prepared in a stoichiometric ratio of Tb:Y:Zr=10:16:74 (molar ratio). The purity of the three oxides is 99.99%. The three oxide raw materials are fully mixed, and the mixture is placed in a high-frequency heater, and the temperature is increased by 5°C per minute until the melting point of the raw material reaches 2750°C, and the temperature is kept for 48 hours, and then the temperature is reduced to room temperature by 10°C. The whole piece of raw material is taken out, and block crystals with high optical quality are selected from it. The crystal is then annealed in a reducing (argon-hydrogen mixed gas) atmosphere at an annealing temperature of 1500°C and kept for 48 hours to obtain a 10at% Tb:Y2O3 / ZrO2 crystal.
[0033] The size of the small crystal before annealing is 26 mm × 50 mm, see Figure 2 , its crystal powder XRD shows Figure 8 , the crystal transmits the spectrum Fig. 9 The crystal maintains high transmittance in the range of 400 nm-1500 nm, up to 80%, due to its Tb 3+ The ion concentration is low and there is no need to test its magneto-optical coefficient.
[0034] Example 2 Growth of 20at% Tb:Y2O3 / ZrO2 Crystals Using Cold Crucible Technology The raw materials are Tb4O7, Y2O3, and ZrO2, which are prepared in a stoichiometric ratio of Tb:Y:Zr=20:14:66 (molar ratio). The purity of the three oxides is 99.99%. The three oxide raw materials are fully mixed, and the mixture is placed in a high-frequency heater, and the temperature is increased by 5°C per minute until the melting point of the raw material reaches 2650°C, and the temperature is kept for 48 hours, and then the temperature is reduced to room temperature by 10°C. The whole piece of raw material is taken out, and block crystals with high optical quality are selected from it. The crystal is then annealed in a reducing (argon-hydrogen mixed gas) atmosphere at an annealing temperature of 1500°C for 48 hours to obtain a 20at% Tb:Y2O3 / ZrO2 crystal.
[0035] Crystal blank (weight 50 Kg) see Figure 3 The size of the small crystal before annealing is 20 mm × 50 mm, and the XRD results of the crystal powder show Figure 8 , the crystal transmits the spectrum Fig.10The crystal maintains high transmittance in the range of 400 nm-1500 nm, with a maximum of 82%, and a magneto-optical Verdet coefficient of 352 rad·m -1 ·T -1 (450 nm), 260 rad·m -1 ·T -1 (505 nm), 138 rad·m -1 ·T -1 (633 nm), 46 rad·m -1 ·T -1 (880 nm), 35 rad·m -1 ·T -1 (1064 nm), see Fig.14 .
[0036] Example 3 Growth of 50at% Tb:Y2O3 / ZrO2 Crystals by Cold Crucible Technology The raw materials are Tb4O7, Y2O3, and ZrO2, and the ingredients are prepared in a stoichiometric ratio of Tb:Y:Zr=50:9:41 (molar ratio). The purity of the three oxides is 99.99%. The three oxide raw materials are fully mixed, and the raw materials are placed in a high-frequency heater, and the temperature is increased by 5°C per minute until the raw material melting point of 2500°C is reached, and the temperature is kept for 48 hours, and then the temperature is reduced to room temperature by 10°C. The whole piece of raw material is taken out, and block crystals with high optical quality are selected from them. The crystal is then annealed in a reducing (argon-hydrogen mixed gas) atmosphere at an annealing temperature of 1500°C and kept for 48 hours to obtain a 50at% Tb:Y2O3 / ZrO2 crystal.
[0037] After annealing, the crystal Figure 6 The crystal is transparent and has no cracks. Figure 4 The blank weighs 50 Kg, and the size of the small crystal before annealing is 25 mm × 40 mm. The XRD results of the crystal powder show Figure 8 , the crystal transmits the spectrum Fig.11 The crystal maintains high transmittance in the range of 400nm-1500nm, with a maximum of 80%, and a magneto-optical Verdet coefficient of 487 rad·m -1 ·T -1 (450 nm), 367 rad·m -1 ·T -1 (505 nm), 227 rad·m -1 ·T -1 (633 nm), 98 rad·m -1 ·T -1 (880 nm), 73 rad·m -1 ·T -1(1064 nm), see Fig.15 .
[0038] Example 4 Growth of 50at% Tb:Y2O3 Crystals by Cold Crucible Technology The raw materials are Tb4O7 and Y2O3, which are prepared in a stoichiometric ratio of Tb:Y=1:1. The purity of both oxides is 99.99%. The two oxides are fully mixed, and the raw materials are placed in a high-frequency heater, and the temperature is increased by 5°C per minute until the melting point of the raw materials reaches 2450°C, which is kept warm for 48 hours, and then reduced to room temperature by 10°C. The whole piece of raw material is taken out, and block crystals with high optical quality are selected from them. The crystals are then annealed in a reducing (argon-hydrogen mixed gas) atmosphere at an annealing temperature of 1500°C for 48 hours to obtain transparent 50at% Tb:Y2O3 crystals.
[0039] The crystal size is 18 mm × 60 mm. Figure 5 , its crystal powder XRD shows Figure 8 , the crystal transmits the spectrum Fig.12 The crystal maintains high transmittance in the range of 400 nm-1500 nm, with a maximum of 81%, and a magneto-optical Verdet coefficient of 564 rad·m -1 ·T -1 (450 nm), 394 rad·m -1 ·T -1 (505 nm), 242 rad·m -1 ·T -1 (633 nm), 106 rad·m -1 ·T -1 (880 nm), 70 rad·m -1 ·T -1 (1064 nm), see Fig.16 .
[0040] Example 5 Growth of Tb2O3 crystals using cold crucible technology The raw material is Tb4O7, and the purity of the oxide is 99.99%. The raw material is placed in a high-frequency heater and heated at 5°C per minute until it reaches the melting point of 2600°C, which is kept warm for 48 hours, and then cooled to room temperature at 10°C. The whole piece of raw material is taken out, and block crystals with high optical quality are selected from it. The crystal is then annealed in a reducing (argon-hydrogen mixed gas) atmosphere at an annealing temperature of 1500°C for 48 hours to obtain Tb2O3 crystals.
[0041] The size of the small crystal before annealing is 27 mm × 17 mm. Figure 7 , its crystal powder XRD shows Figure 8 , the crystal transmits the spectrum Fig.13The crystal maintains high transmittance in the range of 400 nm-1500 nm, with a maximum of 78%, and a magneto-optical Verdet coefficient of 1196 rad·m -1 ·T -1 (450 nm), 801 rad·m -1 ·T -1 (505 nm), 476 rad·m -1 ·T -1 (633 nm), 174 rad·m -1 ·T -1 (880 nm), 149 rad·m -1 ·T -1 (1064 nm), see Fig.17 .
[0042] The scope of protection claimed by the present invention is not limited to the above specific embodiments. For those skilled in the art, the present invention may have various deformations and changes. Any modifications, improvements and equivalent substitutions made within the concept and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A Tb-based cubic magneto-optical crystal, characterized in that: It is Tb 3+ One or a combination of doped Re2O3 and ZrO2, wherein Re is a rare earth element selected from Y, Lu or Sc.
2. The Tb-based cubic magneto-optical crystal according to claim 1, characterized in that: 10%at≤Tb 3+ The doping concentration is ≤98%at.
3. The Tb-based cubic magneto-optical crystal according to claim 2, characterized in that: 20%at≤Tb 3+ The doping concentration is ≤50%at.
4. The Tb-based cubic magneto-optical crystal according to claim 1, 2 or 3, characterized in that: Its magneto-optical Verdet coefficient is 10-149 rad·m -1 ·T -1 (at 1064 nm).
5. The Tb-based cubic magneto-optical crystal according to claim 4, characterized in that: Its magneto-optical Verdet coefficient is 35-73 rad·m -1 ·T -1 (at 1064 nm).
6. The Tb-based cubic magneto-optical crystal according to claim 5, characterized in that: Its light transmission range is 400 nm-1500 nm.
7. The method for preparing the Tb-based cubic magneto-optical crystal according to any one of claims 1 to 4, characterized in that: include: Step 1, weigh the raw materials Tb4O7, Re2O3, and ZrO2 according to the stoichiometric ratio, mix them thoroughly, put them into a high-frequency heater, heat them to near the melting point of the raw materials, and then keep them warm; Step 2, cooling to room temperature, taking out the reactants and selecting block crystals therein; Step three, annealing the bulk crystal obtained in step two in an argon-hydrogen mixed gas atmosphere to obtain the transparent Tb-based cubic phase magneto-optical crystal.
8. The method according to claim 5, characterized in that: In step 1, the temperature is increased at 5°C per minute until it reaches near the melting point of the raw material and is kept at this temperature for 48 hours.
9. The method according to claim 5 or 6, characterized in that: In step 2, the temperature is lowered from 10°C to room temperature.
10. The method according to claim 7, characterized in that: In step three, the annealing conditions are: temperature 1500° C., time 48 hours.
Citation Information
Patent Citations
Terbium oxide crystal for magneto-optic element
JP2011121840A
Crystal of terbium oxide for magneto-optical element
JP2013091601A
Magneto-optical material, method for producing same and magneto-optical device
US20160209683A1